Modelling PRRS transmission between pig herds in Denmark and prediction of interventions impact - You Chang; Ana Rita Pinheiro Marques; Mette Fertner; Nils Toft; Bjørn Lorenzen; Mossa Merhi Reimert; Hans Houe; Beate Conrady (Preventive Veterinary Medicine, 2025)

Bayesian evaluation of temporal changes in sensitivity and specificity of three serological tests for multiple circulating strains of rabbit haemorrhagic disease virus - Kandarp K. Patel; Nils Toft; John Kovaliski; Bradley Page; Ridma M.J. Jayasinghe Ellakkala Appuhamilage; Patrick L. Taggart (Preventive Veterinary Medicine, 2024)

Lipidomes of Icelandic bryophytes and screening of high contents of polyunsaturated fatty acids by using lipidomics approach - Yi Lu; Finnur Freyr Eiriksson; Margrét Thorsteinsdóttir; Nils Cronberg; Henrik Toft Simonsen (Phytochemistry, 2023)

Spatio‐temporal variations in mortality during the seawater production phase of Atlantic salmon ( Salmo salar ) in Norway - Britt Bang Jensen; Lars Qviller; Nils Toft (Journal of Fish Diseases, 2020)
In a sustainable production of animals, monitoring and minimizing mortality must be a top priority. Systematic measuring of mortality over time can be used to evaluate the impact of changes in management and production strategies in Norway. To aid understanding of the potential for reducing mortality, we have used data from 2014 to 2018 to investigate the spatio‐temporal patterns of mortality, by descriptive analyses and statistical modelling of possible determinants of mortality. The results show large differences in mortality across different production zones and between years. The areas with the highest density of farmed salmon are also the ones with highest mortality. The total cumulated mortality of farmed salmon increased from 32.3 million in 2014 to 35.2 million in 2018, corresponding to 14.3% and 15.8% of the standing stock. An initial higher mortality was observed during the first 3 months after stocking (mean: 1.5% [0.9%–8.6%] mortality/month). This was followed by a period of stability and lower mortality (mean: 0.8% [0.9%–3.1%] mortality/month), until month 10, when mortality started to increase again. The month of first stocking, the year of slaughter, production zone and number of months at sea were all found to be statistically significant determinants for mortality, with p ‐values